Meta Analysis: Application of Health Belief Model on Tertiary Preventive Behavior in Type 2 Diabetes Mellitus Patients - Afifah Nur Haliza; Bhisma Murti; Didik Gunawan Tamtomo (Journal of Health Promotion and Behavior, 2024)
Background: Tertiary prevention of DM is taking action on DM sufferers who experience complications to prevent further disability by providing health education to DM sufferers about the importance of drug compliance, diet and exercise. The study aimed to analyze the effectiveness of the Health Belief Model application in improving tertiary preventive behavior in type 2 diabetes mellitus patients. Subjects and Method: This study is a systematic review and meta-analysis study using PICO. P: Patients with Diabetes Mellitus type 2; I: High perceived severity, high perceived benefit, high self-efficacy; C: Low perceived severity, low perceived benefit, low self-efficacy; O: Tertiary preventive behavior. Data collection was obtained from data bases, namely PubMed, Google Scholar, Elsevier and Springer Link. The inclusion criteria used were full-text articles with a cross-sectional design, published from 2013 to 2023, in English, the final results of the study were reported using the Adjusted Odd Ratio. The keywords used are “Health Belief Model” OR “HBM” AND “diabetes” AND “preventive behavior” OR “type 2” Health Belief Model” AND “type 2 diabetes mellitus” AND “Cross Sectional Study”. Articles were analyzed using Review Manager 5.3. Results: Meta-analysis showed the significant results. The study from Ethiopia, Nepal, and China concluded that high perceived severity had a 2.60 times higher influence than low perceived severity on tertiary preventive behavior (aOR= 2.60; 95% CI= 1.06 to 6.37; p= 0.040). Meta-analysis from Ethiopia, Malaysia, China, and Taiwan concluded that high perceived benefits had an influence of 1.76 times higher than low perceived benefits. (aOR= 1.76; 95% CI= 1.09 to 2.82; p= 0.020). The meta-analysis was obtained from Ethiopia, Sudan, India, and China it showed that high self-efficacy has an effect of 2.69 times higher than low self-efficacy (aOR= 2.69; 95% CI= 1.48 to 4.89; p= 0.001). Conclusion: Perceived severity, perceived benefits and self-efficacy increase tertiary preventive behavior in diabetes mellitus.